Determination of Diffusion Coefficients of Mg2+ Ions from Molten LiCl-KCl-MgCl2 - Yeol Ryu, Hyo; Mun Jeong, Sang (Asian Journal of Chemistry, 2014)
The diffusion coefficients of Mg2+ ions at molybdenum electrode in molten LiCl-KCl-MgCl2 at 670 ºC were determined using the cyclic voltammetry, chronoamperometry and chronopotentiometry, which were calculated to be 1.47 × 10-6, 1.23 × 10-6 and 1.67 × 10-6 cm2/s, respectively. The activation energy for the diffusion process of Mg2+ ions was found to be 106.3 kJ/mol. The underpotential deposition (UPD) of Li+ ions on the pre-deposited Mg and the codeposition of Mg2+ and Li+ ions led a formation of liquid Mg-Li solution at a more positive potential than a potential for Li deposition.